2014
DOI: 10.2522/ptj.20130022
|View full text |Cite
|
Sign up to set email alerts
|

A Path Model for Evaluating Dosing Parameters for Children With Cerebral Palsy

Abstract: Dosing of pediatric rehabilitation services for children with cerebral palsy (CP) has been identified as a national priority. Establishing dosing parameters for pediatric physical therapy interventions is critical for informing clinical decision making, health policy, and guidelines for reimbursement. The purpose of this perspective article is to describe a path model for evaluating dosing parameters of interventions for children with CP. The model is intended for dose-related and effectiveness studies of pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 77 publications
0
65
0
4
Order By: Relevance
“…22 . Involving the community is also believed to enhance caregivers' satisfaction and rehabilitation outcomes 11 in providing holistic care to children with special needs.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 . Involving the community is also believed to enhance caregivers' satisfaction and rehabilitation outcomes 11 in providing holistic care to children with special needs.…”
Section: Limitationsmentioning
confidence: 99%
“…3 Furthermore, satisfaction with rehabilitation intervention is an imperative outcome that is believed to influence the emotional well-being of carers and impacts on a child's psychology. 11 Scarcity in caregiver satisfaction and perception of rehabilitation is evident in resource-poor settings such as South Africa, thus this study is crucial in informing research for rehabilitation professionals involved in the management of children with CP. This study's emphasis was focused on caregivers of children with CP who were involved in rehabilitation within a task-shifting approach.…”
Section: Introductionmentioning
confidence: 99%
“…The authors emphasized that a higher dose of training has to be provided over shorter periods of time in order to achieve improved motor skills in children with CP. Gannotti et al 22 reported that intervention types focused on body structures, activity, or the environment acts on a child first through the family, then through the frequency, intensity, and time to yield structural and behavioral changes. As a result, these changes are linked to improvements in functional independence.…”
Section: Discussionmentioning
confidence: 99%
“…A success of a therapy can be defined as one that can provide changes in activities and participation by the ICF (International Classification of Functioning, Disability and Health) model and best quality of life whom receive that (Damiano, 2009;Gannotti, Christy, Heathcock, & Kolobe, 2014) For CP, there is minimal evidence for the neurodevelopmental therapy. However, evidence for the best outcomes were for intensive training and practice task or functionally (Bailes et al, 2011;Bailes, Greve, & Schmitt, 2010;Damiano, 2009).…”
Section: Introductionmentioning
confidence: 99%